COMPARISON OF POLYPEPTIDE PROFILE OF Trypanosoma evansi ISOLATES FROM INDONESIA AND THEIR RELATION TO BIOTYPE AND SENSITIVITY TO TRYPANOCIDAL - Yuniarto, Ichwan; Subekti, Didik T; Cahyaningsih, Umi; Satrija, Fadjar (Jurnal Kedokteran Hewan, 2018)
This study aimed to determine whether the variant or biotype of Trypanosoma evansi can be seen from their polypeptide profiles using 12%sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS PAGE) stained with Brilliant Blue Commasie. The results generally showed thatthe molecular weight (MW) of polypeptides from nine isolates from East Java, Central Java, Banten, South Kalimantan, Central Kalimantan, andLampung provinces were in the range of 85.46 to 15.76 kD and each isolate has different polypeptide profile. Isolates A13 and A14 were isolatedfrom the same place but have different polypeptide profiles. Likewise, isolates S13 and S18 also have different polypeptide profiles despite beingisolated from the same place at the same time. On the other hand, isolate 372, 87, and 06 have different protein profiles but was classified in thesame biotype namely biotype I. Generally, the difference in protein profile actually more related to the biological diversity of the metabolism ofeach Trypanosoma evansi isolate from Indonesia.